EVALUATION OF CITIZEN SCIENCE PARTICIPANTS' SATISFACTION WITH GEOSPATIAL TECHNOLOGY IN SMART GOVERNANCE - Sari, Heni Vidia; Arief, M. Habibullah; Widiyaningtyas, Triyanna (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
IT productivity paradox phenomenon shows that increasing investment in information technology is not always followed by increasing productivity or user satisfaction. In the context of smart governance, citizen science becomes a strategic approach to evaluate the effectiveness of geospatial technology. This study explores the relationship between self-efficacy, spatial abilities, and user knowledge of system quality and information quality and their impact on user satisfaction. The case study was conducted on the Sistem Informasi Penataan Ruang (Si-Petarung) of Malang City. The results showed that self-efficacy has the most dominant influence on system quality with a dominance value of 40.5%, and user knowledge has the greatest impact on information quality with a dominance value of 32.29%. Information quality is also proven to be the most significant factor in increasing user satisfaction with a dominance value of 47.93%. These findings emphasize the importance of individual abilities, system quality, and information quality in supporting the successful implementation of geospatial technology and provide a basis for developing a system that is more inclusive and responsive to user needs.